2021
DOI: 10.3390/polym13040489
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties Related to Extrusion of Polyolefins

Abstract: Rheological properties related to the extrusion of polyolefins are the shear viscosity, the elongational viscosity, the slip velocity and their temperature- and pressure-dependencies. These properties are measured in the rheology lab mainly via a parallel-plate rheometer and a capillary rheometer. Then appropriate rheological models have to be used to account for all these properties. Such models are either viscous (e.g, the Cross model) or viscoelastic (e.g, the K-BKZ model). The latter gives the best fitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…Applying the Cox–Merz rule, as the frequency was replaced by the shear rate, the values of viscosities at shear rates at 100 s −1 tended to lie below 10,000 Pa s [ 84 ]. As the data points for this frequency were measured at the beginning, the loss of PEG was minimal and the values confirmed the processibility of these blends in an extruder at 200 °C [ 82 , 85 , 86 , 87 , 88 , 89 ]. Figure 8 b shows the influence of temperature on the viscosity of blend E3_PEG200_20.…”
Section: Resultsmentioning
confidence: 59%
“…Applying the Cox–Merz rule, as the frequency was replaced by the shear rate, the values of viscosities at shear rates at 100 s −1 tended to lie below 10,000 Pa s [ 84 ]. As the data points for this frequency were measured at the beginning, the loss of PEG was minimal and the values confirmed the processibility of these blends in an extruder at 200 °C [ 82 , 85 , 86 , 87 , 88 , 89 ]. Figure 8 b shows the influence of temperature on the viscosity of blend E3_PEG200_20.…”
Section: Resultsmentioning
confidence: 59%
“…We began the nonisothermal capillary flow simulations with the viscous Cross-WLF model for the orifice die depicted in Figure 1 a ( ), based on the shear viscosities with and without temperature correction. It is known that the contraction flow has an elongational character along the centerline [ 35 , 37 , 46 ] and that a purely viscous model has a much lower elongational viscosity than a viscoelastic model, therefore it is not surprising to see that the viscous Cross-WLF model severely underpredicted the entrance pressure drop [ 35 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. This is illustrated for GPPS in Figure 6 a, where were measured using the 0.2-mm-long orifice die.…”
Section: Resultsmentioning
confidence: 99%
“…This work does not include the infinite-shear-rate viscosity (as an estimable parameter) for the modified Cross model because all the experimental data did not present the characteristic Newtonian plateau of the high shear-rate region. This consideration is regularly used in the literature according to the shear rate range investigated, [4,29] which regularly applies when the polymer melts have high zero-shear viscosity values (≥10 4 Pa s). For the Bird-Carreau and Carreau-Yasuda, this work used 𝜂 ∞ = 1 × 10 −5 Pa s after performing a sensitivity analysis test, which showed that this parameter is not significant (small influence on the results) due to the shear rate range investigated.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…It has been found the shear stress data could be more accurately described over the wide shear rate range by the newly suggested models. The accuracy of curve fitting decreases in the following order: Modified Quemada model, Modified Carreau [ 23,24] 56-76 𝜂 = f(T, p) [4,25] No informed by the authors 𝜂 = f ( λ, T) [ 8,26,27] No informed by the authors 𝜂 = f(MFI) [17] No informed by the authors.…”
Section: Introductionmentioning
confidence: 99%